Effect of Packaging and Storage on Dried Apple Pomace and Fiber Extracted from Pomace. Issue 3 (30th June 2016) - Sharma, PC; Gupta, Anil; Issar, Kanika
Abstract: Apple pomace and fiber extracted from dried pomace were evaluated for its storage stability. The dried pomace obtained after washing and blanching followed by drying in polytunnel drier (45 ± 8C) was packed in gunny and polyethylene (PE) bags and was stored at low (0‐4C) and ambient temperature (13–26C). Storage of dried pomace in PE bags at low temperature was adjudged best and thus preferred with minimum quality changes. Dried pomace stored in PE bags exhibits 4.40% weight loss even after 9 months storage at low temperature as compare to 9.60% weight loss at ambient temperature. Fiber contents (%) were also reported higher in pomace stored in PE bags i.e.; 39.16% as compare to gunny bags 38.98 percent. Fiber contains moisture contents of 15.64% and also exhibited good hydration properties viz., 5.91g/g Water holding capacity (WHC) and 10.33cc swelling capacity even after 6 months of storage irrespective of packaging material and storage temperature. Further, packaging of fiber in glass jars and aluminium laminated bags followed by storage at low temperature shows significant results and thus optimized for storage of apple fiber. Practical Application: The utilization of apple pomace for the preparation of products, not only brings additional income but also reduces the environmental pollution, which is a pre‐requisite for any new enterprise dealing with food processing industry. Further, apple fiber can be used to prepare low calorie products because of the ability of all polysaccharides to bind water due to their good water‐holding capacity. Fibers are known to act as cholesterol lowering agent due to binding of bile acids in the intestine. The fiber extracted from dried apple pomace can successfully be utilized for preparation of fiber‐enriched products like acidophilus yoghurt, fiber‐enriched mango drink, apple beverage etc. The technology thus would be helpful for the industry for commercial exploration.